Media-Mediated Political Literacy: Assessing Information Ecosystem Dynamics and Civic Empowerment in Indonesia's 2024 Electoral Context - Asep Setiawan; Endang Sulastri; Usni; Miftahul Ulum; Dinar Meidiana; Muhammad Isa Asyrofuddin (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This study critically examines the complex relationship between mass media consumption and political literacy in Indonesia as the nation approached its 2024 general election. Employing a qualitative research methodology analysing high-quality secondary data from multiple sources, the study investigates how various media platforms influence citizens' political knowledge, critical thinking skills, and electoral participation readiness. Research findings reveal significant disparities in political literacy across demographic groups, with digital divides reinforcing information asymmetries between urban and rural populations. Social media emerged as a dominant information source for 68% of voters, yet 73% of respondents demonstrated limited ability to identify misinformation. Traditional media retained significant influence among older voters (65+ demographic), while digital platforms dominated youth engagement. The study identified five prevailing patterns of media-influenced political literacy: platform-dependent knowledge variation, algorithmic reinforcement of political polarization, diminished substantive policy discourse, widespread circulation of electoral misinformation, and variable media literacy skills across demographic segments. These dynamics created a fragmented information ecosystem where political literacy was undermined by information overload, partisan media consumption, and digital platform manipulation. The research contributes to media effects theory by proposing a contextually sensitive integrated framework of political literacy development specific to emerging democracies navigating digital transformation. The study recommends coordinated multi-stakeholder approaches to political literacy enhancement, emphasizing critical media consumption skills, platform accountability, and civic education initiatives tailored to Indonesia's unique socio-political context.